Preparation for and Recovery from Hurricanes and Windstorms for Tropical Fruit Trees in the South Florida Home Landscape - Jonathan H. Crane; Carlos F. Balerdi (EDIS)
HS-1066, a 9-page fact sheet by Johnathan H. Crane and Carlos F. Balerdi, discusses pre-hurricane planning and prevention, post hurricane practices, and hurricane tolerances of selected tropical fruit trees. Includes references and tables showing recommended plant heights, flooding tolerance, minimum temperatures, and mean ranges and ambient temperatures for the Homestead Florida area. Published by the UF Department of Horticultural Sciences, April 2007.